Inappropriate supply of antibiotics for common viral infections by community pharmacies in Vietnam: A standardised patient survey - Shukry Zawahir; Hien Thi Thu Le; Thu-Anh Nguyen; Justin Beardsley; Anh Duc Dang; Sarah Bernays; Kerri Viney; Thai Hung Cao; Dorothy Drabarek; Hoang Huy Tran; Son Tu Nguyen; Van Thi Thuy Pham; et al. (Elsevier, 2022)
Summary: Background: This study aimed to evaluate the appropriateness of antibiotic dispensing of private pharmacies in Vietnam. Methods: Standardised patient surveys were conducted in randomly selected community pharmacies across 40 districts in Vietnam. Four clinical scenarios were represented by patient actors: (a) an adult requesting treatment for a sibling with a viral upper respiratory tract infection (URTI), (b) a parent requesting treatment for a child with acute diarrhoea, (c) an adult making a direct antibiotic request, and (d) an adult presenting with an antibiotic prescription. We calculated the proportion of interactions that resulted in inappropriate supply of antibiotics and patient advice. Predictors of inappropriate antibiotic supply were assessed. Findings: Patient actors attended 949 pharmacies, resulting in 1266 clinical interactions. Antibiotics were inappropriately supplied to 92% (291/316) of adults requesting treatment for URTI symptoms, 43% (135/316) for children with acute diarrhoea symptoms and to 84% (267/317) of direct request for antibiotics. Only 49% of pharmacies advised patients regarding their antibiotic use. Female actors were more likely to be given antibiotics than male actors for URTI (aOR 2·71, 1·12-6·60) but not for diarrhoeal disease. Pharmacies in northern Vietnam were more likely than those in southern Vietnam to supply antibiotics without a prescription: for adult URTI (aOR=5·8, 95% CI: 2·2-14·9) and childhood diarrhoea (aOR=3·5, 95% CI: 2·0-6·0) symptoms, but less likely to dispense for direct antibiotics request. Interpretation: Inappropriate antibiotic supply was common in Vietnamese private pharmacies. Multifaceted measures are urgently needed to achieve WHO's global action plan for the optimal use of antimicrobials. Funding: This study was funded by a grant from the Australian Department of Foreign Affairs and Trade.